Monarch Butterfly Conservation Through the Social Lens: Eliciting Public Preferences for Management Strategies Across Transboundary Nations - Solis-Sosa, Rodrigo; Semeniuk, Christina A. D.; Fernandez-Lozada, Sergio; Dabrowska, Kornelia; Cox, Sean; Haider, Wolfgang (Frontiers in Ecology and Evolution, 2019)
The monarch butterfly (Danaus plexippus), an iconic species that migrates annually across North America, has steeply declined in numbers over the past decade. Across the species' range, public, private, and non-profit organizations aim to reverse the monarch decline by engaging in conservation activities such as habitat restoration, larvae monitoring, and butterfly tagging. Urban residents can actively participate in these activities, yet their contribution can also be realized as an electorate body able to influence the design of conservation programs according to their interests. Little is known, however about their preferences towards the objectives and design of international monarch conservation policies. In this paper, we investigate these preferences via a survey design using Discrete Choice Experiments (DCEs) and Latent Class Analysis (LC) of urban residents across the main eastern migratory flyway in Ontario, Canada, and the eastern United States. Attributes in the DCE included the size and trend of overwintering butterfly colonies, the type of institution leading the conservation program, international allocation of funds, and the percentage of funds dedicated to research. From the general populace, we isolated respondents already engaged in monarch conservation activities to explore how they compare. We sent a smaller set of surveys deliberately withholding the expected-success forecast of the monarch recovery program to assess the value of information for urban residents within a conservation context. The LC distinguished three groups of respondents among urban residents: 1) the main group, labelled ‘Eager’, accounting for 72.4% of the sample, that showed a high potential for supporting conservation policies and had remarkable similarities with the monarch enthusiasts' sample; 2) a ‘Pro Nation’ group (18.4%) marked by their increased willingness to support conservation initiatives solely focused within their country of residence; and 3) an ‘Opinionated’ segment (9.23%), that was highly reactive to changes of the leading institution, resources allocation, and economic contribution proposed. Key findings from this research reveal that to maximize potential support amongst urban residents in the monarch’s breeding range, a conservation strategy for the monarch butterfly should be led by not-for-profit organizations, should strive for transboundary cooperation, and should include the communication of anticipated ecological outcomes.